Rekayasa Perangkat Lunak Sistem Ujian TOEFL Menggunakan PHP & MySQL Berbasis Framework CodeIgniter - Dwihana, Yustiar Alan; Bisri, Achmad (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2018)
Abstract–NowadaysTOEFL score is often used as a requirement by universities that have an international curriculum base in the process of admitting new students and requires all students to understand English as a communication tool in the learning process. A large number of prospective students as examinees and the use of written examinations often results in loss and damage to exam data, plus a process of correction of exam results that takes a long time, causing information from various data to be obtained longer. To overcome this problem, a TOEFL exam system software needs to be made. The flow and stages made in software engineering include requirements planning, software design, and software implementation. The use of PHP and My SQL based on framework CodeIgniter on the TOEFL exam has provided convenience to an institution or agency, the positive results in its application took the form of time savings of 3,440 minutes or around 92.5% and reduced stages in the test from 9 stages to only 2 stages. So that the resources, infrastructure, and costs needed in the examination process are reduced.